Behavioural aspects and psychiatric findings in Noonan's syndrome. Issue 2 (February 1995) - Wood, A; Massarano, A; Super, M; Harrington, R
Abstract : This study describes the behavioural phenotype and psychiatric symptoms of 21 children with Noonan's syndrome attending a paediatric genetics clinic. Data from the behavioural phenotypes questionnaire are presented that suggest that children with Noonan's syndrome tend to be clumsy, stubborn, irritable, have communication difficulties, and are 'faddy eaters'. Nearly 50% of the patients with Noonan's syndrome were psychiatric 'cases' as assessed by a standardised measure.